2010
DOI: 10.1128/jvi.01338-10
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Previously Unrecognized Promoter That Drives Expression of the UXP Transcription Unit in the Human Adenovirus Type 5 Genome

Abstract: We previously identified an adenovirus (Ad) protein named U exon protein (UXP) encoded by a leftward-strand (l-strand) transcription unit. Here we identify and characterize the UXP promoter. Primer extension and RNase protection assays mapped the transcription initiation site at 32 nucleotides upstream of the UXP gene initiation codon. A series of viral mutants with mutations at two putative inverted CCAAT (I-CCAAT) boxes and two E2F sites were generated. With mutants lacking the proximal I-CCAAT box, the UXP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…The late regions (L1–L5) are transcribed from an alternatively spliced transcript. Recently, it was shown that the regions encoding the L4-22K and L4-33K proteins are initially expressed at low levels from a novel promoter located within the L4 region [ 24 ], and these proteins act to fully activate the MLP [ 25 ]. There are also four small products produced at intermediate/late times of infection, including the structural protein IX (pIX), and the IVa2 protein that helps package viral DNA into immature virions [ 26 ].…”
Section: Adenovirus Biologymentioning
confidence: 99%
“…The late regions (L1–L5) are transcribed from an alternatively spliced transcript. Recently, it was shown that the regions encoding the L4-22K and L4-33K proteins are initially expressed at low levels from a novel promoter located within the L4 region [ 24 ], and these proteins act to fully activate the MLP [ 25 ]. There are also four small products produced at intermediate/late times of infection, including the structural protein IX (pIX), and the IVa2 protein that helps package viral DNA into immature virions [ 26 ].…”
Section: Adenovirus Biologymentioning
confidence: 99%
“…At 24 hpi, however, viral gene expression shifted to be dominated by late gene expression, as well as early transcripts derived from the E1B locus ( Figure 3B ). At late times post infection we also saw the E3-Fiber transcript, 19K/IX, and E4-DBP transcripts increase dramatically, potentially implicating these messages as novel late transcripts, with expression as abundant as the recently described late UXP transcript [47,48]. Furthermore, while all permutations of the X, Y, and Z leaders preceding Fiber were previously detected by short-read sequencing these could not be phased to full-length transcript isoforms [53,70].…”
Section: Resultsmentioning
confidence: 78%
“…Due to the spurious nature of low-level AdV splicing events [53], we set abundance thresholds for the highly abundant viral late transcripts of 500 reads for short-read junctions, and at least ten events detected in the long-read sequencing when collapsed by FLAIR [69]. Using this method, we readily detected other recently discovered viral isoforms, such as multiple splice sites preceding the pVII ORF [53], the so-called X, Y, and Z leaders embedded in E3 and preceding L5-Fiber [53,70], and the newly described UXP [47,48]. Using full-length RNAs, we were able to detect novel splice sites producing canonical ORFs that only differ in UTRs for L4-100K, L4-33K, L4-pVIII, and E4orf6/7.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The U exon protein (UXP) is expressed from the complementary l-strand of the viral genome from an exon (U) located within E3, with two subsequent exons located in the 100K and DBP coding regions (Table 2) (43). Activation of the U promoter element located in fiber has been shown to occur after, and to be dependent on, Ad genome replication (44). In concordance with these observations, transcripts from U are found at later time points, consistent with late gene transcripts.…”
Section: Early Gene Expression (I) E1mentioning
confidence: 99%